2009
DOI: 10.1155/2009/274740
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic and Anticonvulsant Effects on Mice of Flavonoids, Linalool, and α‐Tocopherol Presents in the Extract of Leaves of Cissus sicyoides L. (Vitaceae)

Abstract: The aim of the present study is to demonstrate the anxiolytic and anticonvulsant effects of a hydroalcoholic extract obtained from the aerial parts of Cissus sicyoides L. (CS) (Vitaceae) on male and female mice using several behavioral assays. Groups of males and females treated via intraperitoneal (IP) with doses of 300, 600, and 1000 mg/kg of the extract showed significant action in the elevated plus-maze (EPM), time spent in the open arms, and number of entries in the open arms. The board-hole test also sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 36 publications
6
26
0
Order By: Relevance
“…It has been mentioned that the antioxidant activity of plants might be due to their phenolic compounds. The phenols with linalool are the major components of OB (57). In the present study, OB extract decreased the level of anxiety in animals.…”
Section: Discussionsupporting
confidence: 65%
“…It has been mentioned that the antioxidant activity of plants might be due to their phenolic compounds. The phenols with linalool are the major components of OB (57). In the present study, OB extract decreased the level of anxiety in animals.…”
Section: Discussionsupporting
confidence: 65%
“…However, Zhang et al23 report that menthol has an anti-epileptic effect, not only in culture but also when administered through intraperitoneal (i.p) injection. Similarly, De Almeida et al22 report that i.p. injection of AIS (linalool, TRPM8 ligand) present in the leaves of Cissus sicyoides can inhibit epileptic activity.…”
Section: Discussionmentioning
confidence: 90%
“…A previous study (Beltrame et al, 2002) showed that two compounds isolated from aerial parts of the plant (β-sitosterol and sitosterol-β-D-glucopyranoside) presented antibacterial activity, while the aqueous extract was able to contract isolated guinea-pig aortic rings by increasing the calcium entry through the membrane and mobilizing the internal calcium deposits (García et al, 1997). Aqueous extract was also shown to present cytostatic (Saenz et al, 2000), antinociceptive (Almeida et al 2006b) and anti-inflammatory (García et al, 2000) effects. In recent study , the methanolic extract obtained from the leaves of C. sicyoides was evaluated for the ability to protect the gastric mucosa against injuries caused by different necrotizing agents in rodents.…”
Section: Cissus Sicyoides L Vitaceae (Insulina-vegetal)mentioning
confidence: 99%
“…In Brazil, C. sicyoides is largely found in Caatinga and used in folk medicine for treatment of several diseases, such as epilepsy, stroke, gastric ulcer, abscesses, as well as it Bioactivity and potential therapeutic benefits of some medicinal plants from the Caatinga (semi-arid) vegetation of Northeast Brazil: a review of the Maria I. G. Silva et al and methylmalonate induced convulsions (Ribeiro et al, 2005) and to prevent the occurrence of epileptic foci in a rat model of posttraumatic epilepsy (Yamamoto et al, 2002). Recently, Almeida et al (2009) demonstrated the anticonvulsant and also anxiolytic effects of a hydroalcoholic extract obtained from the C. sicyoides on mice, probably due to the action of α-tocopherol, flavonoid(s) and linalool present in the leaves. Taken together, the cited studies validate the folkloric use of C. sicyoides as anticonvulsant.…”
Section: Cissus Sicyoides L Vitaceae (Insulina-vegetal)mentioning
confidence: 99%